2007
DOI: 10.1134/s1063776107090075
|View full text |Cite
|
Sign up to set email alerts
|

Generation of linear waves in Bose-Einstein condensate flow past an obstacle

Abstract: The theory of linear wave structures generated in Bose-Einstein condensate flow past an obstacle is developed. The shape of wave crests and dependence of amplitude on coordinates far enough from the obstacle are calculated. The results are in good agreement with the results of numerical simulations obtained earlier. The theory gives a qualitative description of experiments with BoseEinstein condensate flow past an obstacle after condensate's release from a trap.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…with its approximation (19), and corroborate these two curves with numerical solution of the GP equation where we introduce as initial condition the wave profiles shown in the left panel of figure 1. It is remarkable that the asymptotic formula (19) is quite accurate even for not very large values of t along almost all wave packet where |x| > ct (see figure 2).…”
Section: Decay Of a Small Disturbance Of A Stationary State To Linearsupporting
confidence: 77%
See 2 more Smart Citations
“…with its approximation (19), and corroborate these two curves with numerical solution of the GP equation where we introduce as initial condition the wave profiles shown in the left panel of figure 1. It is remarkable that the asymptotic formula (19) is quite accurate even for not very large values of t along almost all wave packet where |x| > ct (see figure 2).…”
Section: Decay Of a Small Disturbance Of A Stationary State To Linearsupporting
confidence: 77%
“…Right panel: comparison of the exact analytic solution (15), asymptotic approximation (19), and numerical solution of the GP equation (37) for the density disturbance, corresponding to t = 4 and c = 2. The initial disturbance has a gaussian form (21) with a = 0.95.…”
Section: Decay Of a Small Disturbance Of A Stationary State To Linearmentioning
confidence: 99%
See 1 more Smart Citation
“…The nature of the medium perturbation and the properties of the induced non-equilibrium interaction are defined by the properties of the medium (e.g., by its nonlinearity) and the mechanism of energy losses. The perturbation can lead to generation of vortices, Cherenkov radiation, or local phase transitions (some more effect can be found in hydrodynamics [1][2][3][4][5][6], optics [7], plasma physics [8][9][10][11][12][13], quantum liquids and Bose condensates [14][15][16][17][18][19][20]). …”
Section: Introductionmentioning
confidence: 99%
“…It was found that the critical velocity at which superfluid behavior breaks down is about V c ∼ = 0.35c s , where c s denotes the sound velocity in a uniform condensate far enough from the obstacle. For the flow velocity above the sound velocity, V > c s , a new channel of dissipation opens-Cherenkov radiation of Bogoliubov waves whose interference results in formation of a specific "ship wave" pattern located, due to the properties of the Bogoliubov dispersion relation, outside the Mach cone [6][7][8][9]. Emission of vortices dominates in the interval of velocities c s < V < 1.43c s where vortices form so-called "vortex streets" located inside the Mach cone.…”
mentioning
confidence: 99%